Efficient Microorganisms in lettuce cultivation - Sousa, Westefann dos Santos; Pontes, José Roberto Verginio de; Melo, Osmanny Francisco Pereira de (Revista Agrogeoambiental, 2020)
Efficient Microorganisms are shown to be an effective, alternative, sustainable, safe, and low-cost technique to increase the productivity of organic foods, and their use is a good option for agroecological management. Based on this context, this work had as main objective to evaluate the efficiency of the application of a biological cocktail from Efficient Microorganisms in the cultivation of lettuce. In the capture of the Efficient Microorganisms and the manufacture of the biological cocktail, a methodology proposal in the agroecology used by Brazilian Ministry of Agriculture, Cattle and Supplying (MAPA, in Portuguese, Ministério da Agricultura, Pecuária e Abastecimento). The adopted experimental design was randomized blocks containing 8 blocks and 3 treatments. The T1 treatment, application of the Efficient Microorganisms, obtained a greater fresh mass of the aerial part of the plants sampled in the two cycles, resulting in a higher productivity in tons/hectare. The results proved to be advantageous for the productivity of the lettuce that received application of the biological cocktail from Efficient Microorganisms, when the biomass parameters were analyzed.